Continuing Professional Development (CPD) Models for Islamic Education Teachers in Malaysia and Indonesia - Abdul Hakim Abdullah; Munawir Munawir (CV. Zamron Pressindo, 2025)
Research Objective – This study aims to examine and compare the models of Continuing Professional Development (CPD) for Islamic education teachers in Malaysia and Indonesia, focusing on their implementation, challenges, and opportunities in enhancing teacher professionalism in the era of globalization and digital education. Methodology – Employing a qualitative comparative case study approach, the research involved semi-structured interviews, document analysis, and limited observations in Islamic secondary schools. Data were collected from 40 participants, including teachers, school leaders, policymakers, and CPD facilitators from both countries. Thematic analysis and policy comparison were used to identify structural patterns and contextual insights. Findings – The study reveals that Malaysia applies a structured, tiered CPD framework with strong institutional support, digital integration, and collaborative school cultures. In contrast, Indonesia’s CPD implementation faces fragmentation, limited contextual adaptation, and infrastructural gaps—especially in rural areas. Both countries encounter resistance to pedagogical change, particularly among Islamic Education teachers rooted in traditional teaching models. Research Implications/Limitations – While offering valuable comparative insights, the study is limited by its qualitative scope and focus on selected institutions. Further research could extend to other Islamic education contexts and evaluate long-term CPD impacts on teaching quality and student learning. Originality/Value – This study contributes original empirical data on CPD in Islamic education, highlighting culturally responsive strategies and institutional models that can inform education policy and professional development frameworks across Muslim-majority countries.